Holomorphic extension of generalizations of Hp functions. II - Richard D. Carmichael (International Journal of Mathematics and Mathematical Sciences)
In a previous article we have obtained a holomorphic extension theorem (edge of the wedge theorem) concerning holomorphic functions in tubes in ℂn which generalize the Hardy Hp functions for the cases 1<p≤2. In this paper we obtain a similar holomorphic extension theorem for the cases 2<p<∞.